Synchronous clear cell renal cell carcinoma and tubulocystic carcinoma: genetic evidence of independent ontogenesis and implications of chromosomal imbalances in tumor progression - Quiroga-Garza Gabriela; Piña-Oviedo Sergio; Cuevas-Ocampo Karime; Goldfarb Richard; Schwartz Mary R; Ayala Alberto G; Monzon Federico A (BMC, 2012)
Abstract Seven percent of renal cell carcinoma (RCC) cases are diagnosed as "unclassified" RCC by morphology. Genetic profiling of RCCs helps define renal tumor subtypes, especially in cases where morphologic diagnosis is inconclusive. This report describes a patient with synchronous clear cell RCC (ccRCC) and a tubulocystic renal carcinoma (TCRC) in the same kidney, and discusses the pathologic features and genetic profile of both tumors. A 67 year-old male underwent CT scans for an unrelated medical event. Two incidental renal lesions were found and ultimately removed by radical nephrectomy. The smaller lesion had multiple small cystic spaces lined by hobnail cells with high nuclear grade separated by fibrous stroma. This morphology and the expression of proximal (CD10, AMACR) and distal tubule cell (CK19) markers by immunohistochemistry supported the diagnosis of TCRC. The larger lesion was a typical ccRCC, with Fuhrman's nuclear grade 3 and confined to the kidney. Molecular characterization of both neoplasms using virtual karyotyping was performed to assess relatedness of these tumors. Low grade areas (Fuhrman grade 2) of the ccRCC showed loss of 3p and gains in chromosomes 5 and 7, whereas oncocytic areas displayed additional gain of 2p and loss of 10q; the high grade areas (Fuhrman grade 3) showed several additional imbalances. In contrast, the TCRC demonstrated a distinct profile with gains of chromosomes 8 and 17 and loss of 9. In conclusion, ccRCC and TCRC show distinct genomic copy number profiles and chromosomal imbalances in TCRC might be implicated in the pathogenesis of this tumor. Second, the presence of a ccRCC with varying degrees of differentiation exemplifies the sequence of chromosomal imbalances acquired during tumor progression. Virtual Slides The virtual slide(s) for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/1790525735655283